Intensitas Penyakit pada Tanaman Ciplukan (Physalis angulata L.) yang Diberikan Kombinasi Perlakuan Pupuk Hayati (Mikoriza) dan Organik: Diseases Intensity of Ciplukan Plants (Physalis angulata L.) Treated with Biological (Mycorrhiza) and Organic Fertilizer - Ratna Dwi Hirma Windriyati (Universitas Widya Gama Mahakam, 2021)
Ciplukan plant is a plant that has potential to be used as a medicinal plant because it has various bioactive contents. Several studies that have been carried out are still limited to the potential, content and benefits of ciplukan plants. The aspect of disease attack on ciplukan plants, there has not been much research, even though this plant has various benefits and is currently being developed. This is what underlies this research. If previous research used organic and chemical fertilizers, it is also necessary to compare using biological fertilizers derived from mycorrhizal fungi against diseases found in ciplukan plants. The stages of the research carried out were planting preparation and application, observation, maintenance and data analysis. The aim of research was to determine the types and symptoms of disease, as well as important diseases-causing pathogens in ciplukan plants and the effect of a combination of biological (mycorrhizal) and organic fertilizers on diseases intensity. The results of the research obtained two types of diseases that occurred in ciplukan plants, namely leaf spot symptoms caused by Cercospora sp. and curly leaf symptoms caused by Cucumber Mosaic Virus (CMV). The combination of mycorrhizal treatment and organic fertilizer (manure) tends to increase the intensity of leaf spot disease and the incidence of curly leaf diseases.